How can optimal skill mix be effectively implemented and why? - Bourgeault, Ivy Lynn; Kuhlmann, Ellen; Neiterman, Elena; Wrede, Sirpa (World Health Organization, 2008)
The publication focuses on the skills and clinical competence of health personnel in Europe and the related policies. Written for professional public.
European Observatory on Health Systems and Policies, ISSN 1997-8065 policy brief
Keywords: personální obsazení a rozvrh; politologie, politika, zdravotní politika; Personnel Selection; management, organizace a řízení zdravotnictví; Health Policy; Europe; výběr pracovníků; Professional Role; Health Personnel; Personnel Staffing and Scheduling; Clinical Competence; zdravotnický personál; Delivery of Health Care; klinické kompetence; zdravotní politika; Evropa; poskytování zdravotní péče; role odborníka